ID 388 – Dynamic alterations of brain network oscillations in a Tau seeding mouse model of Alzheimer's disease. Issue 3 (March 2016) - Ahnaou, A.; Raeymaekers, L.; Biermans, R.; Moechars, D.; Peeraer, E.; Manyakov, N.; Van De Casteele, T.; Kemp, J.A.; Drinkenburg, W.H.
Abstract : Brain networks' oscillations and connectivity are critical for cognitive functions that are altered in Alzheimer's disease (AD). In the rTg4510 mouse model of progressive tauopathy, pathological Tau reduces the activity in a subset of neocortical network neurons leading to cognitive deficits prior substantial neurodegeneration. Here, using a Tau seed injection model, the effect of induction and spread of Tau aggregation pathology on neurophysiological and functional networks connectivity was investigated. Sleep-wake cycle was generally preserved over 24 weeks after the injection of preformed Tau fibrils into the dorsal CA1 hippocampal region. In contrast, enhanced EEG cortical theta oscillations across different vigilance states occurred as from week 8 onwards, which coincides with first signs of neuronal death, while developing seeded Tau pathology is already at maximal level at 4 weeks. Follow-up studies in mice equipped with multiple EEG electrodes are underway to reveal the impact of Tau spreading pathology on (1) coherent activity between frontal cortex and CA1–CA3 networks; (2) cross-frequency coupling in theta and gamma frequency oscillations; (3) information processing as assessed via auditory evoked potentials and evoked oscillations. It is postulated that Tau-induced changes in EEG network dynamics before global spreading may represent an important functional research marker for early stages of AD.